The influence of content-class related videos as a tool to engage the English language learning in students of the intermediate intensive English II course from the Foreign Language department at the University of El Salvador, term I-2018 - Góngora de Cisneros, Clara Elizabeth; López Segovia, Cristóbal Alexander; Funes Ventura, Alan Bladimir (2024)
Around the 1949 's and the 1960's, technology was developed significantly and educators started including taped lectures in their teaching sessions. It was found that using audiovisual instruments motivated students and enhanced their learning experience. The use of interactive and innovative methods continued to expand and soon, new material was designed and incorporated in lessons plans as teachers recognized the high importance of the technology appliance in the English learning process. "A lot of students these days expect information to be presented in a flashy, entertaining way, so videos can help draw them in" says Larry Sanger, executive director of WatchKnowLearn.org, a site that collects education-related videos. Comparing this quote with the Theory of Howard Gardner, the learner can experience a lot by watching an educational video as their visual-spatial, verbal-linguistic, musical-rhythmic among other intelligences are activated depending on the type of individual and his own way to perceive a message. Educators at the University of El Salvador do present videos in their classrooms once in a while; however, they might include them as a common practice without consciously understanding the repercussion or positive effects that its usage provokes.The video could be incorporated as to cover part of the teaching session but not merely adapted to the gaps, levels or individual student’s needs. The students of Intermediate English are in their peak of learning the language, reason why it is imperative to find a way to promote the video and make professors aware of the profound benefits that the implementation could attract.